Brother Jonathan and John Bull build a nation: the transactional nature of American nationalism in the early nineteenth century. Issue 2 (2nd April 2016) - Maguire, Susan E.
Abstract : This article employs a transactional approach to examine the role of national stereotypes in the rise of American nationalism in the late eighteenth and early nineteenth centuries. Despite deep sectional and partisan divisions within the US population, an American national identity was constructed in contrast to the British national character and perceived British ideals. This identity was constructed on an external categorization by the elite males of other nations, particularly England. Political satires and caricatures, particularly in the character of Brother Jonathan and John Bull, illustrate the oppositional nature of this nascent national identity during the early nineteenth century.